Text message reminders for visit adherence among non-communicable disease patients in Haiti: A pilot study. - Calixte Dawson; Sarah M Morris; Evyrna Toussaint; Darius Léopold Fénelon; Bolanle Banigbe; Gene F Kwan (PLOS Global Public Health)
Clinic appointment compliance is a challenge to care continuity for people with chronic non-communicable diseases (NCD) globally. Short-message-service (SMS) text reminders have improved attendance in several settings but have not been tested in Haiti. This pilot study of an SMS reminder strategy to improve clinic attendance for NCD patients in Central Haiti assessed the feasibility and acceptability the messages. We included patients in the NCD clinic - adults with hypertension, type 2 diabetes, and heart failure; and children/young adults with type 1 diabetes (T1D) - at Hôpital Universitaire de Mirebalais. Patients with appointments between December 13-22, 2021, were sent SMS reminders 3 days and 1 day before their visit. Patients completed a survey at their appointment evaluating the usefulness, acceptability, and feasibility of the reminders. We assessed barriers to receiving the SMS and how they influence clinic attendance. Ninety-six patients had a scheduled appointment during the study period. SMS reminders were sent to all patients with recorded phone numbers (91.2%). 72 patients (75%) attended their visit. Half of those who attended their visit received the SMS. Of these patients, 100% liked the reminder, 97.2% wanted to receive future messages, and 22.2% reported they would not have attended their visit without the reminder. Of the 36 patients who did not receive the SMS, 38.9% changed their phone number while 33.3% did not have access to a phone. Barriers to receiving the SMS were inconsistent cellular signal (25%) and lack of access to a phone (22%). Sending SMS reminders was feasible and acceptable to NCD patients. The messages were universally liked by the patients and positively influenced the decision of some to attend their visit. Barriers to uptake include updating phone numbers and access to phones. If implemented at scale, SMS reminders may improve appointment attendance in rural Haiti for those with mobile phones.